Evaluation of the stability of polymeric materials exposed to palm biodiesel and biodiesel-organic acid blends (2018)
ABSTRACT: The aim of the present work is to evaluate the impact of pure palm biodiesel fuel (B100) and biodiesel blends with 0.32% oleic, palmitic, acetic, myristic, and stearic acids on the properties of some polymeric materials used commonly in the manufacture of auto parts such as the polyamide 66 (PA66), polyoxymethylene (POM), and high-density polyethylene (HDPE). The effects of the B100 and B100–acid blends on polymeric materials were examined by comparing changes in the gain/loss of mass and by measuring the hardness, the impact strength, and the tensile strength of the materials at the end of the exposure. The characterization of the polymers was carried out before and after exposure by using differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FTIR). After the immersion in B100–acids blends, the HDPE exhibited an increase in mass of 5%, which was very similar in all blends. The PA66 showed a small decrease in weight (2% approx.) in all mixtures. The POM presented an increase in the percentage of weight in the mixture of B100 with acetic acid of 0.3%. A decrease was observed in the crystallinity of the HDPE when exposed to blends of B100–acids. This behavior may be associated with a plasticizing effect in the HDPE exposed to the blends. The mechanical properties of POM and HDPE showed no significant changes after immersion in the fuels. On the other hand, PA66 exhibited a significant decrease in maximum stress value after immersion in B100, B100–oleic acid and B100–palmitic acid blends. The variation of the mechanical properties of the PA66 after exposure to B100 was potentiated by addition of organic acids. The assessed polymers did not undergo appreciable changes in the chemical structure of the samples after immersion in the fuels, so the variation in the mechanical properties could be explained by physical absorption of the fuel into the polymers.